Arte de derecho - Llull, Ramon (Historia del Derecho, 2011)
This book includes the first translation of the treatise Ars de iure (1304) by Ramon Llull into a modern language. This translation into Spanish by Pedro Ramis Serra and Rafael Ramis Barceló, accompanied with notes trying to clarify the legal, conceptual and philosophical scope of the lullian conception of Law. The preliminary study by Rafael Ramis Barceló is an introduction to the life, work and thought of Llull, who pays attention to the political and legal context of Llull and the main concepts of the work: general principles of law, theory of justice and natural law. This is one of the most important treatises of legal epistemology throughout the Middle Ages and an alternative vision to the ratio scripta model of ius commune in Montpellier and the Mediterranean Kingdoms. = Este libro incluye la primera traducción del tratado Ars de iure (1304) de Ramon Llull a un idioma moderno. Esta traducción al español, debida a Pedro Ramis Serra y a Rafael Ramis Barceló, se acompaña con notas que intentan precisar el alcance jurídico, termonológico y filosófico de la concepción del derecho de Ramon Llull. El largo estudio preliminar de Rafael Ramis Barceló es una introducción a la vida, obra y pensamiento de Llull, que presta atención al contexto político-jurídico luliano, así como a los conceptos principales de la obra: principios generales del derecho, teoría de la justicia y derecho natural. Se trata de uno de los tratados de epistemología jurídica más importantes de toda la Edad Media y una visión alternativa al modelo de la ratio scripta del ius commune en Montpellier y en los reinos del Mediterráneo.